2019
DOI: 10.1101/730762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

De novowhole-genome assembly in interspecific hybrid table grape, ‘Shine Muscat’

Abstract: This study presents the first genome sequence of an interspecific grape hybrid, 'Shine Muscat' (Vitis labruscana × V. vinifera), an elite table grape cultivar bred in Japan. The complexity of the genome structure, arising from the interspecific hybridization, necessitated the use of a sophisticated genome assembly pipeline with short-read genome sequence data. The resultant genome assemblies consisted of two types of sequences: a haplotype-phased sequence of the highly heterozygous genomes and an unphased sequ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Recently, Di Genova et al (2014) reported a draft genome sequence of V. vinifera table grape 'Sultanina' (synonym of 'Thompson Seedless') and identified a large number of structural variants and SNPs in comparison with the reference genome of the wine grape 'Pinot Noir' (line PN40024). Shirasawa et al (2019) reported the de novo whole-genome sequence of interspecific hybrid table grape, 'Shine Muscat', and identified potential structural variants between the genomes of 'Shine Muscat' and 'PN40024'. These differences probably reflect the genetic divergence between table, wine, and rootstock grapes (Aradhya et al 2003).…”
Section: Distribution Tendency Of Myb Genotypes In "Utilization" Categorymentioning
confidence: 99%
“…Recently, Di Genova et al (2014) reported a draft genome sequence of V. vinifera table grape 'Sultanina' (synonym of 'Thompson Seedless') and identified a large number of structural variants and SNPs in comparison with the reference genome of the wine grape 'Pinot Noir' (line PN40024). Shirasawa et al (2019) reported the de novo whole-genome sequence of interspecific hybrid table grape, 'Shine Muscat', and identified potential structural variants between the genomes of 'Shine Muscat' and 'PN40024'. These differences probably reflect the genetic divergence between table, wine, and rootstock grapes (Aradhya et al 2003).…”
Section: Distribution Tendency Of Myb Genotypes In "Utilization" Categorymentioning
confidence: 99%
“…Despite de novo genome assembly methods are being developed since more than two decades [14], only recently the community started focusing on highly heterozygous genomes [15][16][17][18][19][20][21]. Typically, high amounts of sequence variation between alleles prevent contig extension and scaffolding.…”
mentioning
confidence: 99%